Hospital Pharmaceutical Inventory Control in In-Vitro Fertilization Services Using Minimum-Maximum Stock Level - Paramesthi, Prasasya; Jati, Sutopo Patria; Suryoputro, Antono (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2024)
Type C "X" Specialized Hospital in Semarang experienced in vitro fertilization (IVF) and embryology laboratory consumable medical supplies (CMS) stockouts in early 2023, delaying medical care. Minimum-maximum stock level (MMSL) is an alternative pharmaceutical inventory procurement method. Compared to the conventional method, this study examined how well the MMSL method controls IVF medications and embryology laboratory CMS at Hospital “X” Department of Pharmacy. This study is a quantitative, secondary data-based, quasi-experimental, non-equivalent study without a control group. The study sampled all IVF medications and embryology laboratory CMS data from October to December 2023 at Hospital “X” with consistent supply. MMSL was implemented prospectively in January – March 2024. Twelve (12) IVF medications and fifty-six (56) embryology laboratory CMS were studied. Efficiency analysis included inventory value, inventory turnover ratio (ITOR), and stockout value; effectiveness analysis included stockout incidences. Statistics were tested using Wilcoxon signed-rank and McNemar tests. MMSL implementation led to increased inventory value of IVF medications (from IDR21,514,537.00 to IDR49,635,116.00, p=0.040, p<0.05), decreased inventory value of embryology laboratory CMS (from IDR117,421,582.00 to IDR105,318,804.00, p=0.005, p<0.05), and increased ITOR of embryology laboratory CMS (from 0.82 to 0.84 times, p=0.040, p<0.05). MMSL significantly improved IVF medications and embryology laboratory CMS inventory management efficiency.